Host-Toxoplasma gondii Coadaptation Leads to Fine Tuning of the Immune Response - Brasil, Thaís Rigueti; Freire-de-Lima, Celio Geraldo; Morrot, Alexandre; Vetö Arnholdt, Andrea Cristina (Frontiers in Immunology, 2017)
Toxoplasma gondii has successfully developed strategies to evade host’s immune response and reach immune privileged sites, where remain in a controlled environment inside quiescent tissue cysts. In this review, we will approach several known mechanisms used by the parasite to modulate mainly the murine immune system at its favor.In what follows, we review recent findings revealing interference of host’s cell autonomous immunity and cell signaling, gene expression, apoptosis and production of microbicide molecules such as nitric oxide and oxygen reactive species during parasite infection. Modulation of host’s metalloproteinases of extracellular matrix is also discussed. These immune evasion strategies are determinant to parasite dissemination throughout the host taking advantage of cells from the immune system to reach brain and retina, crossing crucial hosts’ barriers.